Image steganography using uncorrelated color space and its application for security of visual contents in online social networks - Muhammad, Khan; Sajjad, Muhammad; Mehmood, Irfan; Rho, Seungmin; Baik, Sung Wook (Future generation computer systems, 2018)
Image steganography is a growing research field, where sensitive contents are embedded in images, keeping their visual quality intact. Researchers have used correlated color space such as RGB, where modification to one channel affects the overall quality of stego-images, hence decreasing its suitability for steganographic algorithms. Therefore, in this paper, we propose an adaptive LSB substitution method using uncorrelated color space, increasing the property of imperceptibility while minimizing the chances of detection by the human vision system. In the proposed scheme, the input image is passed through an image scrambler, resulting in an encrypted image, preserving the privacy of image contents, and then converted to HSV color space for further processing. The secret contents are encrypted using an iterative magic matrix encryption algorithm (IMMEA) for better security, producing the cipher contents. An adaptive LSB substitution method is then used to embed the encrypted data inside the V-plane of HSV color model based on secret key-directed block magic LSB mechanism. The idea of utilizing HSV color space for data hiding is inspired from its properties including de-correlation, cost-effectiveness in processing, better stego image quality, and suitability for steganography as verified by our experiments, compared to other color spaces such as RGB, YCbCr, HSI, and Lab. The quantitative and qualitative experimental results of the proposed framework and its application for addressing the security and privacy of visual contents in online social networks (OSNs), confirm its effectiveness in contrast to state-of-the-art methods. •A secure framework for ensuring the security of visual contents in online social networks.•Image scrambling using a light-weighted image scrambler before data embedding.•Encryption of sensitive contents using iterative magic matrix-based encryption algorithm.•Data hiding using an adaptive LSB substitution method.